Strategi Engagement Instagram @Kumocake.Co dalam Mempertahankan Citra Japanese Cake - Faiha Alya; Afni , Hana; Patrianti, Tria (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
This study aims to analyze the social media engagement strategy of Instagram @kumocake.co in its efforts to maintain its product image as ‘Japanese Halal Cake for 25,000 Rupiah’ amid fierce competition in the culinary industry. The method used is descriptive qualitative, with data collection through in-depth interviews with social media specialists, observation, and documentation. The results show that the engagement strategy is implemented in a structured manner through a monthly content plan with weekly execution, as well as consistent uploads every two days in alternating Reels and feed formats. The most effective Instagram features are Stories for direct interaction and Reels for expanding audience reach, which consistently meet audience gratification needs in accordance with Uses and Gratifications Theory (UGT). The product image is maintained through eye-catching, neat, and minimalist visual highlights of the cake in each content, in line with the principles of Brand Image Theory. The highest level of engagement is achieved through endorsement and giveaway content, where save and share metrics are considered the most significant indicators of engagement. Despite facing challenges with the quality of non-preservative products, Kumocake.co manages them with a relaxed and fast response interaction strategy. This research contributes to the development of Digital Public Relations studies, particularly regarding the strategic role of social media engagement in the process of maintaining the image of contemporary culinary products.